2017
DOI: 10.1016/j.ajog.2016.12.177
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural outcomes comparing fibroid embolization and focused ultrasound: a randomized controlled trial and comprehensive cohort analysis

Abstract: Background Uterine fibroids are a common problem for reproductive-aged women, yet little comparative effectiveness research is available to guide treatment choice. Uterine artery embolization and magnetic resonance imaging–guided focused ultrasound surgery are minimally invasive therapies approved by the United States Food and Drug Administration for treating symptomatic uterine fibroids. The Fibroid Interventions: Reducing Symptoms Today and Tomorrow study is the first randomized controlled trial to compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…Two studies compared MR-HIFU to UAE [17,31], and they reported lower reintervention rates and greater improvement in symptoms after UAE. However, the mean NPV% in both trials was below 50% [32]. More recent studies reported lower retreatment rates: 12.7% after MR-HIFU at 19.4 months (comparable to UAE) [13,28].…”
Section: Discussionmentioning
confidence: 70%
“…Two studies compared MR-HIFU to UAE [17,31], and they reported lower reintervention rates and greater improvement in symptoms after UAE. However, the mean NPV% in both trials was below 50% [32]. More recent studies reported lower retreatment rates: 12.7% after MR-HIFU at 19.4 months (comparable to UAE) [13,28].…”
Section: Discussionmentioning
confidence: 70%
“…Fifty-eight partially RPPTs from 2005 onwards were found, of which 44 (including 24 873 patients) were eligible for at least basic data extraction (table 1), and 20 could be included in the meta-analyses (PRISMA flow chart, figure 1). 15–72 Exclusion reasons for the meta-analyses were: no availability of both treatment outcomes in the randomised and preference cohorts separately in 14 trials,15 16 18 19 23 24 27 30 31 34 39 41 42 63 no availability of SDs, which could also not be converted from other available data in five trials,21 29 49 52 62 and the number of events or the power of one or both cohort(s) was too low to perform separate randomised and preference analyses in five trials 25 28 40 55 72. The trials covered a wide range of clinical areas and interventions.…”
Section: Resultsmentioning
confidence: 99%
“…109 In comparison with UAE, MRgFUS has a shorter recovery time and less need for pain medication, but treatment times are longer. 123 A 2017 review of pregnancy outcomes and MRgFUS in the literature documents 102 pregnancy reports after this procedure. Forty-seven were full-term deliveries, 1 was a planned delivery at 36 weeks secondary to placenta previa, 21 were spontaneous abortions, 22 were elective terminations, and 11 were ongoing pregnancies.…”
Section: Magnetic Resonance Imaging-guided Focused Ultrasound Surgerymentioning
confidence: 99%